(untitled) (Ustozlar uchun, 2025)
In this article, the distribution areas of the saffron plant and the climate adaptation of the species in each distribution area, and the change in medicinal properties are highlighted. Also, information about the saffron plant, its systematic place, and alleged diseases were disclosed.